Development of a Computer Vision-Based Auto-Scroll Guitar Chord Application Using Motion Detection - M. Zikry Sahendra Chan; Qatrunnada Athirah Herdiyanto; Chelsea Febiola Sebayang; Debi Yandra Niska (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2026)
The development of computer vision technology enables the creation of a more natural human-computer interaction system through the use of body movements as a control medium. One of the problems often faced by users of digital guitar chord applications is the process of navigating the chord display which is still done manually so that it can interfere with guitar playing activities. This study aims to design and implement a computer vision-based AutoChord application that utilizes head movement detection as a control medium to automatically auto-scroll the guitar chord display. The research method used is the Waterfall software development method which includes the stages of system requirements analysis, system design, implementation, and system testing. The system was developed using webcam-based facial detection technology to read changes in the user's head orientation in real-time. The results of the study show that the AutoChord application is able to automatically run the chord display navigation function through the user's head movements so that it can increase the comfort and efficiency of user interaction when playing the guitar. Thus, the developed system can be an alternative solution in supporting guitar playing activities based on computer vision interaction